Coronary Artery CTA A Case-Based Atlas (Springer International Publishing, 2018)
The second edition of this important work provides a broad range of cardiac CT angiography (CCTA) cases covering normal anatomy, congenital coronary anomalies, coronary artery disease, percutaneous coronary intervention, postsurgical coronary revascularization, and extra-coronary abnormalities. It is designed to help practicing radiologists, cardiologists, and cardiothoracic surgeons understand the current issues involved with clinical, interventional, and surgical management of coronary artery CTA. Each case consists of detailed CCTA images, a brief history, diagnosis, discussion, and pearls and pitfalls. This updated and expanded edition includes new chapters on principles of cardiac CT, patient preparation, cardiomyopathies, pediatric cardiac CT, cardiac CT in the emergency department, CT-FFR, and reporting cardiac CT.